Paediatric Erdheim-Chester Disease in the Lateral Ventricle: A Case Report and Review of the Literature - Ma, Yimei; Guo, Xia; Wan, Zhi; Liu, Hanmin; Gao, Ju (Frontiers in Oncology, 2022)
Erdheim-Chester disease (ECD) is a rare non-Langerhans cell histiocytosis caused by the expression of CD68-positive and CD1a-negative foam tissue cells, which is polar in pediatric patients. The study reports a case of an 8-year-old Chinese boy who presented with polydipsia and polyuria for 4 years, followed by central nervous system symptoms. Magnetic resonance imaging (MRI) showed a large lesion in the lateral ventricle. The histiocytes stained positively for CD68 and negatively for CD1a and langerin, and were partially positive for S100 by immunohistochemical assay. More importantly, BRAFV600E staining was positive in tissue, and the BRAFV600E mutations was also detected by real-time quantitative PCR (RT-qPCR) in the intracranial lesion tissue. According to our review of the literature, this is the first case of ECD in the ventricle, with a younger age. The case is rare compared to those previously reported.